PENGARUH TINGKAT KONFORMITAS KELOMPOK DAN KONSEP DIRI TERHADAP PERSEPSI PERNIKAHAN PADA GENERASI MILENIAL - Ramadhani Putri Utami; wiwid Noor Rakhmad (Interaksi Online, 2026)
This study analyzes the influence of group conformity level and self-concept on marriage perception among millennials in Semarang City. The rising trend of marriage postponement among millennials underlies the urgency of this research. A quantitative approach was applied to millennial respondents (born 1981–1996) delaying marriage via purposive sampling, analyzed using multiple linear regression. Results show that group conformity has a significant negative influence on marriage perception, meaning stronger conformity to marriage-delaying group norms leads to more negative marriage perception. Conversely, self-concept has a significant positive influence, where individuals with stronger self-esteem and self-confidence tend to hold more positive marriage perceptions. Together, both variables contribute significantly in explaining the variation in marriage perception among millennials. The study recommends strengthening self-concept and developing critical attitudes toward group norms to form a more balanced marriage perception.